Association of interferon-γ and interleukin 10 genotypes and serum levels with partial clinical remission in type 1 diabetes - Alizadeh, B Z (Blackwell Science Inc, 2006)
We studied whether serum interferon (IFN)-γ or interleukin (IL)-10 levels and their corresponding functional polymorphic genotypes are associated with partial remission of type 1 diabetes (T1D). A multi-centre study was undertaken in patients with newly diagnosed T1D and matched controls. T1D patients were followed for 3 months and characterized for remission status. Partial clinical remission was defined as a daily insulin dose ≤ 0·38 units/kg/24 h with an HbA1c ≤ 7·5%. Thirty-three patients and 32 controls were phenotyped for serum concentrations of IFN-γ and IL-10 and genotyped for functional polymorphisms of the IFN-γ and IL-10 genes. Sixteen of 25 informative patients (63%) remitted. Serum IFN-γ concentrations were significantly decreased in remitters but increased in non-remitters compared to controls, and did not change over time in any group. IFN-γ genotypes corresponded with serum levels in controls and non-remitters, but not in remitters who displayed the lowest serum IFN-γ levels despite more often carrying high-producing IFN-γ genotypes. Neither the frequency of IL-10 genotypes nor serum IL-10 concentration differed between patients and controls. The combination of high-producing IFN-γ genotype together with low serum IFN-γ concentration at the time of diagnosis provided a strong positive predictive value for remission. Serum IFN-γ concentrations predicted by genotype and observed serum levels were discordant in remitters, suggestive of regulation overruling genetic predisposition. Although high-producing genotypes were less frequent in remitters, they were predictive of remission in combination with low serum IFN-γ levels. These data imply that remission is partially immune-mediated and involves regulation of IFN-γ transcription.